Comparing the response modulation hypothesis and the integrated emotions system theory: The role of top-down attention in psychopathy. (1st February 2018) - Munneke, Jaap; Hoppenbrouwers, Sylco S.; Little, Bethany; Kooiman, Karen; van der Burg, Erik; Theeuwes, Jan
Abstract: Objective: Two major etiological theories on psychopathy propose different mechanisms as to how emotional facial expressions are processed by individuals with elevated psychopathic traits. The Response Modulation Hypothesis (RMH) proposes that psychopathic individuals show emotional deficits as a consequence of attentional deployment, suggesting that emotional deficits are situation-specific. The Integrated Emotions System theory (IES) suggests that psychopathic individuals have a fundamental amygdala dysfunction which precludes adequate responsiveness to the distress of others. Methods: Participants performed a visual search task in which they had to find a male target face among two female distractor faces. Top-down attentional set was manipulated by having participants either respond to the face's orientation, or its emotional expression. Results: When emotion was task-relevant, the low-scoring psychopathy group showed attentional capture by happy and fearful distractor faces, whereas the elevated group showed capture by fearful, but not happy distractor faces. Conclusion: This study provides evidence for the RMH such that top-down attention influences the way emotional faces attract attention in individuals with elevated psychopathic traits. However, the different response patterns for happy and fearful faces suggest that top-down attention may not determine the processing of all types of emotional facial expressions in psychopathy. Highlights: Here, two influential but opposing etiological theories of psychopathy are empirically tested. We test emotional versus attentional deficits in psychopathy. Top-down attention set influences emotion perception in psychopathy. Different emotional expressions are not processed equally by psychopathic individuals.